2013
DOI: 10.1177/0194599813482289
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Retropharyngeal Calcific Tendinitis (Longus Colli Tendinitis) in the General Population

Abstract: Retropharyngeal calcific tendinitis is not a rare disease and is probably underdiagnosed because symptoms are nonspecific, treating physicians are often unfamiliar with this entity, and it is a self-limiting pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 16 publications
0
52
0
3
Order By: Relevance
“…Oropharyngeal in these patients is completely normal inspection and odynophagia pertaining to patients is typically lateralized [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oropharyngeal in these patients is completely normal inspection and odynophagia pertaining to patients is typically lateralized [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…It typically occurs at the top level of C1-C2. The deposit of hydroxyapatite in the sinewy muscle insertion may result in symptomatic tendinitis which is often diagnosed accidentally, since it has an atypical clinic neck pain associated with swallowing pain [4,7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The first from Danish Chiropractors Hviid et al attempted to retrospectively determine the number of cases, of which they found 45 from 1989 to 2006 [5]. Although the study admits to several shortcomings causing them not to find a true prevalence, Horowitz et al [9] through a more systematic approach found eight new cases over a 3-year period compared to only one documented retropharyngeal abscess. They calculated the incidence of retropharyngeal tendonitis to be 0.50 cases per 100,000 persons-year, challenging whether this was indeed as rare as previously thought [9].…”
Section: Discussionmentioning
confidence: 99%
“…Given its propensity to present that way, calcific tendinitis of the longus colli should be recognized when characteristic features are present. This condition is a rare, but probably underrecognized [1] form of calcium hydroxyapatite deposition disease [2]. The entity was first described by Hartley in 1964 [3] and later proven histologically to be due to calcium hydroxyapatite by Ring and his colleagues in 1994 [4].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of calcific tendinitis of the longus colli muscle is unknown. It is estimated by some to be around 0.5 per 100,000 persons per year [1], but is probably underestimated because it is a little known self-limiting entity. As in the other forms of calcium hydroxyapatite deposition disease [2], its cause is incompletely understood.…”
Section: Discussionmentioning
confidence: 99%